Culture and the much-more-than-human: the case of colloids - Szerszynski Bronislaw (Cultural Science)
In this paper I try to identify a minimal definition of culture that might be applicable in the much-more-than-human realm that extends beyond organic matter and human involvement. I speculate that culture conceived in this broad way might be a metapattern or ‘machinic solution’ available to matter of diverse kinds, organic and inorganic. I explore how this idea might apply this to colloids – hybrid forms of matter such as sols, foams and gels that are mixtures of matter in different phase states, some continuous and some discontinuous, and which can behave in complex ways that mix features of solid and fluid behaviour. I conclude by suggesting that attending to both the similarities and differences between ‘culture’ in the organic and in the inorganic realms might force us to rethink our understanding of both.